Solventing out crystallization-basic magnesium carbonate percipitation for thorough phosphorus removal from ammonium tungstate solution - Yang, Liang; Qu, Jie; Gong, Dandan; Wang, Zhongbing; Wang, Ruixiang; Wan, Linsheng (Frontiers in Chemistry, 2022)
The ammonium tungstate solution obtained by leaching scheelite with phosphate contains a large amount of phosphorus. For production of qualified ammonium paratungstate products, phosphorus must be deeply removed from the ammonium tungstate solution. In this study, a novel process for ammonium phosphate recovery and deep phosphorus removal from the solution was proposed. First, ammonium phosphate was crystallized and separated from the ammonium tungstate solution by blowing ammonia and cooling. Results showed that the crystallization ratio of phosphorus was above 95% under the conditions of an ammonia concentration of 4.18 mol/L, an initial phosphorus concentration ranging from 15 g/L to 30 g/L, a holding time of 60 min and the temperature of 20 °C. Then, the small portion of phosphorus remaining in the ammonium tungstate solution was further deeply removed by basic magnesium carbonate percipitation. The phosphorus removal efficiency was above 99 % and tungsten loss was less than 0.22% under the following conditions: the basic magnesium carbonate stoichiometric ratio was 1.5, the initial phosphorus concentration was ranging from 0.5 to 4 g/L, the reaction time was 120 min and temperature was 25 °C. After phosphorus removal, the concentration of phosphorus in the ammonium tungstate solution was below 10 ppm, which meant deep phosphorus removal was achieved.